Eyeball Pressure Stimulation Unveils Subtle Autonomic Cardiovascular Dysfunction in Persons with a History of Mild Traumatic Brain Injury - Hilz, Max-Josef; Aurnhammer, Felix; Flanagan, Steven R.; Intravooth, Tassanai; Wang, Ruihao; Hoesl, Katharina M.; Pauli, Elisabeth; Koehn, Julia (Journal of Neurotrauma, 2015)
After mild traumatic brain injury (mTBI), patients have increased long-term mortality rates, persisting even beyond 13 years. Pathophysiology is unclear. Yet, central autonomic network dysfunction may contribute to cardiovascular dysregulation and increased mortality. Purely parasympathetic cardiovascular challenge by eyeball pressure stimulation (EP), might unveil subtle autonomic dysfunction in post-mTBI patients. We investigated whether mild EP shows autonomic cardiovascular dysregulation in post-mTBI patients. In 24 patients (34 ± 12 years; 5-86 months post-injury) and 27 controls (30 ± 11 years), we monitored respiration, electrocardiographic RR intervals (RRI), systolic and diastolic blood pressure (BPsys, BPdia) before and during 2 min of 30 mm Hg EP, applied by an ophthalmologic ocular pressure device (Okulopressor(®)). We calculated spectral powers of RRI in the mainly sympathetic low frequency (LF; 0.04-0.15 Hz) and parasympathetic high frequency (HF; 0.15-0.5 Hz) ranges, and of BP in the sympathetic LF range, the RRI-LF/HF ratio as index of the sympathetic-parasympathetic balance, normalized (nu) RRI-LF- and HF-powers, and LF- and HF-powers after natural logarithmic transformation (ln). Parameters before and during EP in post-mTBI patients and controls were compared by repeated measurement analysis of variance with post hoc analysis (p < 0.05). During EP, BPsys and BPdia increased in post-mTBI patients. Only in controls but not in post-mTBI patients, EP increased RRI-HFnu-powers and decreased RRI-LF-powers, RRI-LFnu-powers, BPsys-LF-powers, BPsys-lnLF-powers and BPdia-lnLF-powers. RRI-LF/HF ratios slightly increased in post-mTBI patients but slightly decreased in controls upon EP. Even with only mild EP, our controls showed normal EP responses and shifted sympathetic-parasympathetic balance towards parasympathetic predominance. In contrast, our post-mTBI patients could not increase parasympathetic heart rate modulation but increased BP upon EP, indicating a paradox sympathetic activation. The findings support the hypothesis that central autonomic dysfunction might contribute to an increased cardiovascular risk, even years after mTBI.
EVALuna2:22373